Regionalism in Design Development Contemporary Mosque Architecture in Indonesia - Juwono, Sudarmawan; Rukayah, Siti; Lutfiana, Nuraini; Ali, Abdullah (Research and Development Institution, Darussalam Institute for Islamic Studies, 2023)
The architectural designs of contemporary mosques in Indonesia show varied designs, including international modern designs or Middle Eastern-Indian-European models with geometric patterns. This condition indirectly shows that modernism or neo-modernism which is rooted in Middle Eastern culture as a cultural expression is considered to be more representative of Islamic culture than local culture. From the perspective of architectural design and cultural thinking, this is interesting to explore to find out how far regionalism is an alternative for developing Islamic architectural identity in Indonesia. The method used in the research is a qualitative approach by observing and comparing mosque architectural phenomena and exploring architectural elements. The results of the study show that regionalism can accommodate the creative development of Islamic architecture which embodies the values​​of Islamic teachings and environmental identity, the historical context of the people and the spirit of progress contained in the expression of modernity. This concept of thought is in line with al-urf's thinking which provides opportunities for local architectural elements to become part of typical Islamic culture. This design thinking is expressed in the form of post-modern architecture: (1) An architectural concept that integrates local and international cultural forms in concrete form, (2) An architectural concept that emphasizes spirited abstraction in accommodating the values​​of Islamic teachings and local culture in the aim of obtaining optimal benefits. Key words: al-urf, local culture, regionalism.